Increased IgA antibodies to cytokeratins in the spondyloarthropathies. Issue 6 (June 1994) - Borg, A A; Nixon, N B; Dawes, P T; Mattey, D L
Abstract : OBJECTIVES–Increased levels of IgA antibodies to cytokeratin-18 (CK-18) and epidermal keratins (EpK) in the sera of patients with rheumatoid arthritis (RA) have been demonstrated previously. In the present study investigations were carried out to determine whether levels of these autoantibodies were also raised in the spondyloarthropathies, and whether there was any association with particular disease manifestations. METHODS–Using specific enzyme linked immunosorbent assays (ELISA) measurements were taken of IgA, IgG and IgM antibodies to EpK and to CK-18 in the sera of patients with psoriatic arthropathy, ankylosing spondylitis (AS), Reiter's syndrome, psoriasis and in normal subjects. RESULTS–IgA antibodies to both EpK and CK-18 were significantly increased in sera from patients with psoriasis and psoriatic arthropathy but not in the sera from the patients with AS or Reiter's syndrome, or in the controls. In psoriatic arthritis, however, these levels were significantly higher only in those patients with peripheral joint disease and not in those with axial arthritis alone. There was no significant increase in antibody levels in patients with AS or Reiter's syndrome. There were no differences in the levels of IgG or IgM antibodies to CK-18 or EpK between the patient groups and controls. CONCLUSIONS–Raised levels of IgA antibodies to CK-18 and EpK in psoriatic arthropathy and psoriasis probably reflect exposure of intracellular cytokeratin antigens to the immune system after damage to cytokeratin containing cells, and suggests a common pathogenic mechanism in these conditions which involves production of cytokeratin autoantibodies. In patients with psoriatic arthropathy, such a mechanism appears only to be operating in patients with peripheral joint involvement and not in those with axial arthritis.